First-Time Psychotic Symptoms in a Patient After COVID-19 Infection—A Case Report - Łoś, Kacper; Kulikowska, Joanna; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2021)
A 39-year-old, previously healthy, white male with no personal or family history of mental illness, presented with new, first-time psychotic symptoms. The new psychotic symptoms appeared on patient admission to the hospital, occurring during a diagnosis of symptomatic SARS-COV-2 infection. On the first day of hospitalization for worsening psychotic symptoms and the appearance of aggression towards the staff, patient was transferred to the Psychiatric Hospital. After the initial treatment with antipsychotics and benzodiazepines, his mental condition improved. The patient was then transferred for further treatment of his somatic condition in the internal medicine ward, with a recommendation to continue treatment in the Psychiatric Ward once his somatic condition was stabilized. This is one of the few reported cases of COVID-19-related psychosis in a patient without a personal or family history moreover, this description contains important data regarding elevated IL-6, which may prove to be a key factor in the induction of new psychotic symptoms. It indicate the important need, for careful monitoring of neuropsychiatric symptoms among COVID-19 patients.